Public understanding of coercive control in Northern Ireland - Lagdon, Susan (Journal of family violence, 2023)
Coercive control is characterised by negative behaviours which intimidate, threaten, and humiliate a person or restrict a person’s liberty. In addition to being a known risk factor for experiencing other forms of violence, research has linked coercive control to symptoms of psychological distress and suicidality. In the UK, coercive and controlling behaviours within intimate and familial relationships have been legislated as offending behaviours. However, there still exists a lack of international evidence on wider public knowledge and understanding of coercive control. The Northern Ireland Life and Times Survey (NILT) is an annual cross-sectional representative survey of social policy topics. Participants are adults aged 18 years or over. Concerning coercive control, respondents were presented with two relationship scenarios: obvious and less obvious coercive control. Following each scenario, respondents indicated their level of agreement to ten statements covering attitudes towards coercive control, victims of coercive control, talking about coercive control, and whether coercive control is a crime. Respondents indicated whether they had heard of the term ‘coercive control’. Predictors of coercive control awareness were assessed using multinomial logistic regression. Mixed analysis of variance assessed if agreement levels to the ten statements varied by type of coercive control and victim gender. Most respondents said that they had heard of the term coercive control and knew what it meant. Those who had not heard of coercive control at all were more likely to be on a lower income, less qualified and younger, when compared to those who said they knew what the term meant. Significant interactions between coercive control type and victim gender were evident for all ten statements. While most respondents are aware of the term coercive control, a significant number have not and are therefore unlikely to recognise the signs of this type of abuse.